2022
DOI: 10.3389/fnagi.2021.800377
|View full text |Cite
|
Sign up to set email alerts
|

Low-Frequency vs. Theta Burst Transcranial Magnetic Stimulation for the Treatment of Chronic Non-fluent Aphasia in Stroke: A Proof-of-Concept Study

Abstract: BackgroundAlthough low-frequency repetitive transcranial magnetic stimulation (LF-rTMS) has shown promise in the treatment of poststroke aphasia, the efficacy of high-frequency rTMS (HF-rTMS) has yet to be determined.PurposeWe investigated the efficacy of intermittent theta burst stimulation (iTBS) in ameliorating chronic non-fluent aphasia and compared it with that of LF-rTMS.MethodsWe randomly assigned patients with poststroke non-fluent aphasia to an ipsilesional iTBS (n = 29), contralesional 1-Hz rTMS (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…A total of 33 published RCTs using TBS in stroke rehabilitation have reported results and carried out the corresponding analysis. In detail, the results included the following: [ 17 19 ] three for cognitive impairment, [ 9 13 , 20 22 ] eight for visuospatial neglect, [ 23 26 ] four for aphasia, [ 27 38 ] twelve for spasticity and upper extremity/hand motor dysfunction, [ 39 42 ] four for lower extremity/balance and [ 43 , 44 ] two for dysphagia.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…A total of 33 published RCTs using TBS in stroke rehabilitation have reported results and carried out the corresponding analysis. In detail, the results included the following: [ 17 19 ] three for cognitive impairment, [ 9 13 , 20 22 ] eight for visuospatial neglect, [ 23 26 ] four for aphasia, [ 27 38 ] twelve for spasticity and upper extremity/hand motor dysfunction, [ 39 42 ] four for lower extremity/balance and [ 43 , 44 ] two for dysphagia.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…In the convalescent phase, the excitability of the bilateral hemispheres of the brain tends to be balanced, and ITBS may reduce the compensatory effect of the contralateral hemisphere by inhibiting the excitability of the contralateral hemisphere ( 33 ), thereby hindering the functional recovery after stroke, so its efficacy may be worse than ≥10 Hz HF-rTMS. Chou et al ( 43 ) also recommended the application of HF-rTMS in patients with stroke patients during the convalescent phase, considering its mechanism of action and potential adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…An important consideration is whether SLT should be paired with rTMS. Several studies suggested that when employed as a standalone therapy, rTMS holds promise in producing language improvements in PSA ( 6 , 18 20 ). On the contrary, the suggestion that rTMS could prime the brain for behavioral therapy, implying that it should be integrated with SLT, is met with challenges.…”
Section: Introductionmentioning
confidence: 99%